Letter of credit transmission process of Nestlé Bangladesh limited and various factors affecting it - Ali, Tannaz Tasnuva (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.